Students’ Writing Ability on English Descriptive Text at Grade VIII in SMPN 33 Padang - Jayanti, Ade Dwi (ENGLISH FRANCA : Academic Journal of English Language and Education, 2019)
There are 5 indicators in writing descriptive texts such as: identification, description, use of language, vocabulary and mechanics. Based on the problems found at the beginning of the research, the purpose of this research was to find the students ability in writing descriptive text on English subject in SMPN 33 Padang. The type of research is descriptive research. Participants of the research were VIII’s grade students at SMPN 33 Padang. Data obtained through writing descriptive text tests. The data is analyzed by combining Heaton’s theory of assessment in writing and research rubrics about writing. The results of the research concluded that students’ ability in writing identification was Good to Average, students’ ability in writing descriptive was Fair to Poor, students’ ability in language use was Very Poor, students’ ability in using vocabulary was Fair to poor, and students’ ability in using mechanics was Fair to Poor. Then, the results of the research also showed that students had difficulty in identifying objects clearly, difficulties in developing related ideas, students’ lack of understanding of simple present tense structures, limited vocabulary, and errors in mechanics.                                 Keywords: Writing Ability, English Descriptive text